Neuromuscular adaptations to long term vs periodic inclusion of isometric training - Lum, D.; Joseph, R.; Ong, K.; Tang, J.; Suchomel, T. (27th Annual Congress of the European College of Sport Science (ECSS), Sevilla, 30. Aug - 2. Sep 2022, 2022)
INTRODUCTION: The inclusion of isometric training (ISO) has been reported to improve strength and the performance various sports related skills (Lum and Barbosa, 2019; Lum et al., 2021). However, no study has compared the adaptations to long term (>24 weeks) and periodic inclusion of ISO. The aim of the study was to compare the effects of including isometric training for consecutive 24 weeks (CISO) against a periodic inclusion (PISO) of this mode of training, on strength and dynamic performances.